Effectiveness of chewable toothbrushes compared to manual toothbrushes in removing dental plaque - A systematic review and meta-analysis - Hunny Sharma; Manisha Ruikar (Wolters Kluwer Medknow Publications, 2022)
Objective: Chewable toothbrushes (CT) are considered an effective tool for dental plaque removal; however, their effectiveness is still uncertain compared to Manual toothbrushes (MT). Aim: To evaluate the effectiveness of CT compared to MT in dental plaque removal. Methods: Studies comparing the efficiency of CT and MT in dental plaque removal measured by Turesky Modification of Quigley-Hein Plaque Index (TMQHI), Quigley-Hein Plaque Index (QHI), or Silness Loe Plaque Index (SLPI) were identified in PubMed, Medline Web of Science, Google Scholar, and the CENTRAL. Results and effect sizes estimate are presented as mean difference, and subgroup analysis is presented separately for non-randomised interventional studies and randomised intervention studies. Risk of bias was assessed using the Cochrane risk of bias tool (ROBINS-I and ROB2 tool). Results: A total of 10 studies were included in the systematic review, whereas six out of 10 studies were included in the meta-analysis. Both CT and MT were effective in plaque reduction over time when compared individually using the TMQHI and SLPI scores. The overall pooled summary showed no difference in CT and MT's dental plaque removal ability when measured using the TMQHI score. Similarly, there was no difference in CT and MT's dental plaque removal ability when measured using the SLPI score. Conclusion: There is no significant difference in CT and MT's plaque removal ability. Therefore, CT should only be recommended for children and individuals with a disability or manual dexterity. Objective: Chewable toothbrushes (CT) are considered an effective tool for dental plaque removal;